Cardiorespiratory-gated cardiac proton radiotherapy using a novel ultrasound guidance system - Keith A Cengel; Zayne Belal; Michele M Kim; Sarah Hagan; Saskia Camps; Alexander Kalinin; Weihow Hsue; Eric Diffenderfer; Adriano Garonna; Cory Tschabrunn (Clinical and Translational Radiation Oncology)
Cardiac stereotactic body radiotherapy is a promising noninvasive treatment for patients with refractory ventricular tachycardia. With the aim to prove feasibility of a novel image guided radiotherapy and heart motion gating device, cardiac proton radiotherapy was performed using a porcine model. Using a novel adaptation of γ − H2AX tissue staining techniques, we have been able to localize a radiation beam in large animal tissue to assess targeting accuracy within a defined field. Cardiorespiratory-gated irradiations of the animals were successfully completed and analysis of the γ-H2AX staining intensity of the excised heart after radiation demonstrated radiotherapy was delivered close to or within the expected region. We simulated the irradiated volumes under different gating scenarios, showing significant reduction when using combined cardiorespiratory gating. The results of this study show the feasibility of proton irradiation of the heart left ventricle with a novel ultrasound based cardiorespiratory gating technology with the benefit of reduced irradiation volumes and increased healthy tissue sparing.